Astaxanthin supplementation counters exercise-induced decreases in immune-related plasma proteins - Nieman, David C.; Woo, Jongmin; Sakaguchi, Camila A.; Omar, Ashraf M.; Tang, Yang; Davis, Kierstin; Pecorelli, Alessandra; Valacchi, Giuseppe; Zhang, Qibin (Frontiers in Nutrition, 2023)
Objectives: Astaxanthin is a dark red keto-carotenoid found in aquatic animals such as salmon and shrimp, and algae (Haematococcus pluvialis). Astaxanthin has a unique molecular structure that may facilitate anti-oxidative, immunomodulatory, and anti-inflammatory effects during physiological stress. The primary objective of this study was to examine the efficacy of 4-weeks ingestion of astaxanthin in moderating exercise-induced inflammation and immune dysfunction using a multi-omics approach. Methods: This study employed a randomized, double blind, placebo controlled, crossover design with two 4-week supplementation periods and a 2-week washout period. Study participants were randomized to astaxanthin and placebo trials, with supplements ingested daily for 4 weeks prior to running 2.25 h at close to 70%VO2max (including 30 min of 10% downhill running). After the washout period, participants repeated all procedures using the counterbalanced supplement. The astaxanthin capsule contained 8 mg of algae astaxanthin. Six blood samples were collected before and after supplementation (overnight fasted state), immediately post-exercise, and at 1.5h-, 3h-, and 24h-post-exercise. Plasma aliquots were assayed using untargeted proteomics, and targeted oxylipin and cytokine panels. Results: The 2.25 h running bout induced significant muscle soreness, muscle damage, and inflammation. Astaxanthin supplementation had no effect on exercise-induced muscle soreness, muscle damage, and increases in six plasma cytokines and 42 oxylipins. Notably, astaxanthin supplementation countered exercise-induced decreases in 82 plasma proteins (during 24h recovery). Biological process analysis revealed that most of these proteins were involved in immune-related functions such as defense responses, complement activation, and humoral immune system responses. Twenty plasma immunoglobulins were identified that differed significantly between the astaxanthin and placebo trials. Plasma levels of IgM decreased significantly post-exercise but recovered after the 24h post-exercise recovery period in the astaxanthin but not the placebo trial. Discussion: These data support that 4-weeks astaxanthin versus placebo supplementation did not counter exercise-induced increases in plasma cytokines and oxylipins but was linked to normalization of post-exercise plasma levels of numerous immune-related proteins including immunoglobulins within 24h. Short-term astaxanthin supplementation (8 mg/d during a 4-week period) provided immune support for runners engaging in a vigorous 2.25h running bout and uniquely countered decreases in plasma immunoglobulin levels.